2016
DOI: 10.1016/j.celrep.2016.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Gene Function Prediction Based on Developmental Transcriptomes of the Two Sexes in C. elegans

Abstract: SUMMARY We compare whole-animal RNA-seq transcriptomes for C. elegans males and hermaphrodites from the late L3 larval stage to young adulthood. During this interval, male sexual structures develop, including extensive neurogenesis and synaptogenesis that nearly doubles the size of the nervous system. Previous genome-wide expression studies in C. elegans have usually focused on only one sex—the hermaphrodite—and there are a relatively large number of genes that remain without meaningful annotation. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 61 publications
(82 reference statements)
7
55
0
Order By: Relevance
“…To further investigate if there are sex-specific differences in the expression of the germline pattern genes, we examined differential gene expression in the pooled male and hermaphrodite datasets using DESeq2 (Love et al, 2014). We found that 1274 genes were >2 fold enriched in hermaphrodites (adjusted p value < 0.1) and 3895 genes in males, which corresponds well with bulk RNA sequencing data (Kim et al, 2016). We found that 789 of the germline pattern genes were >2 fold enriched in hermaphrodites, 211 (27%) of which were only identified in the hermaphrodite expression maps (Fig.…”
Section: Spatial Gene Expression Analysis Identifies Sexually Dimorphsupporting
confidence: 54%
See 4 more Smart Citations
“…To further investigate if there are sex-specific differences in the expression of the germline pattern genes, we examined differential gene expression in the pooled male and hermaphrodite datasets using DESeq2 (Love et al, 2014). We found that 1274 genes were >2 fold enriched in hermaphrodites (adjusted p value < 0.1) and 3895 genes in males, which corresponds well with bulk RNA sequencing data (Kim et al, 2016). We found that 789 of the germline pattern genes were >2 fold enriched in hermaphrodites, 211 (27%) of which were only identified in the hermaphrodite expression maps (Fig.…”
Section: Spatial Gene Expression Analysis Identifies Sexually Dimorphsupporting
confidence: 54%
“…We could detect an average of 16394 genes in hermaphrodites and 16994 in males, with a total 18778 and 19241 genes in the combined datasets, respectively. This represents 93% and 95.3% of genes that were detected in a recent study using bulk RNA sequencing of young adult hermaphrodites and males (Kim et al, 2016).…”
Section: Generation Of High-resolution Transcriptome-wide Anteropostmentioning
confidence: 92%
See 3 more Smart Citations